Attitudes and entrepreneurship behaviors of students of Józef Piłsudski University of Physical Education in Warsaw - Fąk, Tadeusz; Jarecka, Paulina (Journal of Education, Health and Sport, 2017)
Entrepreneurship is a major competency on the labour market. The goal was, first of all, to recognize the extent to which students are characterized by entrepreneurship. The diagnostic survey method has been applied to gather necessary empirical evidence. The research was conducted in 2016 in a group of 133 students of tourism and recreation Faculty at the Józef Piłsudski University of Physical Education in Warsaw. According to the result analysis more than a half of the respondents' endeavours are characterised by due entrepreneurship.